ANALISIS KUALITAS LAYANAN DAN PENGGUNA APLIKASI OVO TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN PIECES FRAMEWORK - Ni Wayan Wardani; Ni Kadek Ayu Nirwana; Luh Putu Rara Ayu Ratnaningrum; Sita Haniyatus Salimah (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2023)
The OVO application is an application that provides payment system services that can provide convenience in non-cash transactions, besides that the OVO application also opens access to digital financial products and services. OVO application which is a payment system used by various users. The diversity of these users will be an important point in assessing customer satisfaction because each customer has a different level of satisfaction. Users of the OVO application will assess customer satisfaction satisfied or dissatisfied, so that the existing system, will require further development in the future. One of the methods used in measuring the level of customer satisfaction is the pieces framework method which method has variables of performance assessment, information, economy, control, efficiency, and service. Researchers use questionnaires on 103 respondents who use the OVO application, INSTIKI students class of 2019, dissemination of this questionnaire through the Google form platform. The research results on the level of customer satisfaction showed the results of PUAS, with an average value above 4.06.